2015
DOI: 10.1111/hepr.12575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of native vitamin D3 supplementation on refractory chronic hepatitis C patients in simeprevir with pegylated interferon/ribavirin

Abstract: Native vitamin D3 supplementation improved SVR rates in simeprevir with PEG IFN/ribavirin for chronic hepatitis C genotype 1b patients with refractory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Further large trials are required. Third, except for one study , the overall methodological quality of the included trials in the present study was low. Fourth, the included trials analysed data on the basis of surrogate outcomes such as SVR instead of reporting clinical outcomes such as the complications of cirrhosis, decompensation of cirrhosis, hepatocellular carcinoma, extra‐hepatic manifestations and mortality.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Further large trials are required. Third, except for one study , the overall methodological quality of the included trials in the present study was low. Fourth, the included trials analysed data on the basis of surrogate outcomes such as SVR instead of reporting clinical outcomes such as the complications of cirrhosis, decompensation of cirrhosis, hepatocellular carcinoma, extra‐hepatic manifestations and mortality.…”
Section: Discussionmentioning
confidence: 78%
“…All participants received a standard HCV regimen (Peg‐ IFN ‐α and RBV) as antiviral therapy for CHC except for the study by Atsukawa et al . in which participants received simeprevir as a DAA in addition to a standard regimen.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized controlled trial of pegylated IFN‐α2a/ribavirin therapy with cholecalciferol (native vitamin D) versus alfacalcidol (active vitamin D) showed that cholecalciferol could provide superior potentiation of anti‐HCV activity to alfacalcidol during the early phase of treatment through upregulation of serum 25(OH) D3 levels . Previous studies reported that an increase in serum 25(OH) D3 levels through native vitamin D3 supplementation significantly improved SVR rates in pegylated IFN/ribavirin therapy for compensated cirrhotic patients and pegylated IFN/ribavirin/simeprevir for refractory chronic hepatitis C patients . A meta‐analysis also showed that low vitamin D status is associated with a lower likelihood of achieving SVR following pegylated IFN/ribavirin therapy .…”
Section: Discussionmentioning
confidence: 99%
“…A further decrease in serum vitamin D levels reduces the effects of IFN‐based combination therapy for chronic hepatitis C . Conversely, several clinical studies reported that addition of vitamin D to IFN‐based combination therapy improves the SVR rate …”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly recognized that vitamin D could be highly associated with chronic liver diseases especially in chronic hepatitis C (CHC) . However, the role of vitamin D and genetic factors of its related metabolic pathway in CHB infection is less clear.…”
Section: Introductionmentioning
confidence: 99%